Agreement between Ki-67 Proliferative Index in Breast Cancer by Conventional Hotspot Method and International Ki-67 in Breast Cancer Working Group Global Scoring Method: A Cross-sectional Study - Nidhi Radhakrishnan; Padma Priya Kasukurti; Sulata M Kamath; Clement Wilfred Devadass; SR Mangala Gouri (Journal of Clinical and Diagnostic Research)
Introduction: The role of the Ki-67 Proliferative Index (PI) in the molecular classification and as a predictive and prognostic biomarker in breast cancer is definitive. To address the inconsistency in Ki-67 interpretation and scoring, the International Ki-67 in Breast Cancer Working Group (IKWG) introduced the visual scoring Android Application (APP) and proposed a standardised scoring method. Aim: To determine Ki-67 proliferative indices by both the Global Method (GW) with the Ki-67 visual scoring app recommended by IKWG and conventional institutional Hotspot Method (HM), and to analyse the agreement between the indices obtained by these two methods. Materials and Methods: A cross-sectional study involving 71 Ki-67 immunostained hormone receptor-positive trucut biopsies of breast cancers from January 2022 to January 2024 were retrospectively collected. Two observers independently scored the biopsies using HM and GW by an app in the Department of Pathology of a tertiary care centre. The GW scores of Ki-67 PI obtained were categorised into low, intermediate and high groups based on 2015 St. Gallen guidelines. A two-way random Intraclass Correlation Coefficient (ICC) was used to assess the absolute agreement between two scorers. Results: The overall intraclass correlation between interobserver values by HM was 0.819 (good), while it was 0.971 (excellent) by GW. The overall interobserver mean difference was five times greater (p-value=0.008, statistically significant) than the overall interobserver global weighted scores (p-value=0.901, not statistically significant). Conclusion: The study highlighted the significant interobserver variability in HM compared to GW scores by the app. The standardised app scoring method has the potential to broaden the prognostic role of Ki-67 as a companion diagnostic tool.